BUSINESS MANAGERS IN DIFFERENT ENVIRONMENTS: STRATEGY FOR SURVIVAL OF OUTSOURCING THE COMPANY MANUFACTURING AND SERVICES TO LOW-COST LABOUR MARKET - Wibowo, Edwin Agung (Universitas Riau Kepulauan, 2013)
This study defines views of outsourcing from Finland to India. The conventional benefits and disadvantages of outsourcing are reviewed through the multinational Company Nokia moving its manufacturing to India. Particular aim is to address the cultural dimensions relating to outsourcing. Hofstede’s cultural dimensions are used to address this issue, where his study results for Finland and India are used for comparison. In addition, the study draws ethical issues into consideration when a company decides upon outsourcing. Finally, successful strategy on cultural basis is constructed to draw attention on how to return on investment calculations. In whole, the discussion analyses how culture affects outsourcing, the implications and solutions.